Sorghum: An Underutilized Cereal Whole Grain with the Potential to Assist in the Prevention of Chronic Disease - Stefoska-Needham, A.; Beck, E.; Johnson, Stuart; Tapsell, L. (Taylor and Francis Inc., 2015)
Sorghum is an important cereal grain food, grown globally, that is rich in nutrients, dietary fiber, and bioactive components yet is considered of low value to humans and often used as an animal feed. This review provides an overview of key sorghum grain components, including starches, dietary fiber, protein, lipids, and phytochemicals, with functional properties that have potential to impact on health. Though acknowledging the impact of the whole food will reflect the synergy between the components, studies of these components implicate effects on energy balance, glycemic control, lipids, gut microbiota, and cell-mediated immune responses, including antioxidant and anti-inflammatory effects. For these to be confirmed as contributory effects from sorghum consumption, evidence from quality randomized controlled trials is required. If proven effective, there may be a role for sorghum grain–based diets to assist in the prevention of chronic diseases such as diabetes, obesity, and heart disease. Future research addressing effects of sorghum consumption may help drive a paradigm shift from sorghum as a low value food to a potentially health-promoting, highly valued human grain food.